Competition and Security of Supply: Let Russia Buy into the European Gas Market! - Friedel Bolle; Rostyslav Ruban (European University Viadrina, Department of Business Administration and Economics, 2007)
We propose a model of the European gas market where the risk that Russian deliveries are interrupted is endogenized. While Russia's attempts to buy considerable parts of the European downstream industry have faced strong political opposition, we argue that Russian participation in the downstream market would decrease consumer prices and increase the security of supply.
Keywords: 330; Gas; Security of supply; competition; Gaswirtschaft; Direktinvestition; Russisch; Erdgasmarkt; Wettbewerb; Energieversorgung; EU-Staaten; Theorie